Bioinspired nanoantennas for opsin sensitization in optogenetic applications: a theoretical investigation. Issue 2 (6th April 2021) - Keck, Carl H C; Rommelfanger, Nicholas J; Ou, Zihao; Hong, Guosong
Abstract: Opsins with high sensitivity are desired to reduce dependence on optical fibers and enable deep-brain optogenetic stimulation through the intact scalp and skull, while minimizing brain tissue heating and the associated biasing of neural activity. While optimized opsin engineering has produced ultrasensitive and red-shifted opsins suitable for transcranial optogenetic stimulation, further improvements in sensitivity are throttled by biological limitations. Nanostructures are capable of generating near-field intensity enhancements of over 10 4, but thus far nanomaterials have not been applied to amplify local light intensity for optogenetic applications. In this manuscript, we propose the use of bowtie nanoantennas for local enhancement of 470 nm light to sensitize channelrhodopsin (ChR2) to low light intensities. We begin with a comparison of the near-field intensity enhancement offered by different metals at 470 nm, before selecting aluminum as the optimal material. Next, we tune the geometric parameters of aluminum bowtie nanoantennas to maximize the intensity enhancement at 470 nm. We further optimize enhancement by constructing bowtie nanoantenna arrays inspired by patterns occurring in biology, obtaining intensity enhancements up to a factor of 5000. Monte Carlo simulations suggest that transcranial 470 nm illumination of only 50 mW mm −2 is capable of stimulating bowtie-sensitized ChR2 in the deep brain (∼5 mm) in mice, enabling minimally invasive deep-brain stimulation with opsins found in the traditional optogenetic toolbox. This computation-guided optical antenna engineering approach opens opportunities for designing multifunctional materials for enhancing the efficiency of optogenetic neuromodulation, optical neural activity imaging, and highly localized electrical microstimulation in the brain.